Immunology : understanding the immune system - Elgert, Klaus D. (Wiley-Liss, 1996)
A comprehensive and extremely accessible textbook written by a professor with over 20 years of experience teaching immunology courses. Elgert carefully melds together biology, clinical science, genetics and molecular biology of the immune system to provide a coherent and complete account of our knowledge of immunology. A variety of pedagogical aids, including chapter outlines, objectives and summaries as well as a self-evaluation section, assist students in the learning process.